Role of Licochalcone A in Potential Pharmacological Therapy: A Review - Li, Meng-Ting; Xie, Long; Jiang, Hai-Mei; Huang, Qun; Tong, Rong-Sheng; Li, Xiang; Xie, Xin; Liu, Hong-Mei (Frontiers in Pharmacology, 2022)
Licochalcone A (LA), a useful and valuable flavonoid, is isolated from Glycyrrhiza uralensis Fisch. ex DC., and widely used clinically in traditional Chinese medicine. We systematically updated the latest information on the pharmacology of LA over the past decade from several authoritative internet databases, including Web of Science, Elsevier, Europe PMC, Wiley Online Library, and PubMed. A combination of keywords containing “Licochalcone A," "Flavonoid," and "Pharmacological Therapy" was used to help ensure a comprehensive review. Collected information demonstrates a wide range of pharmacological properties for LA, including anticancer, anti-inflammatory, antioxidant, antibacterial, anti-parasitic, bone protection, blood glucose and lipid regulation, neuroprotection, and skin protection. LA activity is mediated through several signaling pathways, such as PI3K/Akt/mTOR, P53, NF-κB, and P38. Caspase 3 apoptosis, MAPK inflammatory, and Nrf2 oxidative stress signaling pathways are also involved with multiple therapeutic targets, such as TNF-α, VEGF, Fas, FasL, PI3K, AKT, and Caspases. Recent studies mainly focus on the anticancer properties of LA, which suggests that the pharmacology of other aspects of LA will need additional study. At the end of this review, current challenges and future research directions on LA are discussed. This review is divided into three parts based on the pharmacological effects of LA for the convenience of readers. We anticipate that this review will inspire further research.